Quantification of Wine Mixtures with an Electronic Nose and a Human Panel - Aleixandre, Manuel; Cabellos, Juan M.; Arroyo, Teresa; Horrillo, M. C. (Frontiers in Bioengineering and Biotechnology, 2018)
In this work, an electronic nose and a human panel were used for the quantification of wines formed by binary mixtures of four white grape varieties and of two varieties of red wines at different percentages (from 0 to 100% in 10% steps for the electronic nose and from 0% to 100% in 25% steps for the human panel). The wines were prepared using the traditional method with commercial yeasts. Both techniques were able to quantify the mixtures tested, but it is important to note that the technology of the electronic nose is faster, simpler and more objective than the human panel. In addition, better results of quantification were also obtained using the electronic nose.